2017
DOI: 10.1016/j.wsj.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chemical additives on consistency, infiltration rate and swelling characteristics of bentonite

Abstract: Problems associated with expansive soils in Egypt are predominantly related to the presence of montmorillonite clay minerals in the soil with fresh water. In this paper we are trying to solve the swelling problem of bentonite by using the chemical additives such as ammonium chloride, sodium chloride sodium carbonate and lime. This paper presents the results of an experimental investigation performed to quantify the effect of mixing bentonite which represent the swelling soil in homogenies phase with chemical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 11 publications
(8 reference statements)
2
8
0
Order By: Relevance
“…It is composed of a disc fixed to a rod with a load of 136 gm slides alongside of the rod, falls from 150 mm height and comes to strike the disc to compact the mixture. Therefore, to prepare the expansive soil-additive mixture samples for testing, these samples were oven dried at 105ºc [1], then weighted according to the maximum dry unit weight of the soil and the chosen percentage of additive and physical mixing for 10 minutes to each portion was adopted. Finally, the weighted amount of the mixture is compacted using the tool described previously in two layers with the same compaction energy.…”
Section: Testing Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…It is composed of a disc fixed to a rod with a load of 136 gm slides alongside of the rod, falls from 150 mm height and comes to strike the disc to compact the mixture. Therefore, to prepare the expansive soil-additive mixture samples for testing, these samples were oven dried at 105ºc [1], then weighted according to the maximum dry unit weight of the soil and the chosen percentage of additive and physical mixing for 10 minutes to each portion was adopted. Finally, the weighted amount of the mixture is compacted using the tool described previously in two layers with the same compaction energy.…”
Section: Testing Methodologymentioning
confidence: 99%
“…Swelling soils is the generic description of all soils containing montmorillonite mineral. Swelling soil deposits are mainly found near the arid areas of Egypt including the regions extending around the Nile valley in Upper Egypt [1]. Swelling soils, also known as expansive soils or reactive soils, composed predominantly of high percentage of fine-grained clay particles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gupta and Sharma (2014) investigated the effect of adding micro silica fume on the shear strength of expansive soil used as subgrade material for construction of exible pavements in rural roads with low tra c volume. Elmashad (2017) performed an experimental investigation was performed to quantify the effect of mixing bentonite as an expansive soil with chemical additives such as sodium chloride, lime, sodium carbonate and ammonium chloride. Also, the effect of polyvinyl alcohol and potassium carbonate on improving the expansive soil was discussed (Zhang et al, 2019) A review of the emerging trends in expansive soil stabilization such as chemical techniques and solid wastes was studied by Ikeagwuani and Nwonu (2019).…”
Section: Introductionmentioning
confidence: 99%
“…According to the research on the damage mechanism of expansive soil subgrade ( Hu et al., 2019 ; Elmashad and Eldin, 2017 ; Anifowose, 1996 ), it is found that the damage of expansive soil subgrade is mainly caused by rainfall, especially when the rain penetrates the subgrade bottom and contacts the extended soil cushion, a thick fluffy layer will be produced. As a highly hydrophilic soil, bentonite can quickly form an ultra-high capillary water elevation line ( Rafalski, 1994 ; Nurus et al., 2016 ; Lubelli et al., 2013 ).…”
Section: Introductionmentioning
confidence: 99%